PROSES MANUFAKTUR MESIN PEMIPIL JAGUNG - Susilawati, S; Ardin, Masri Bin; Sri Wibawa, Subrata Subekti; Septiana, Ryan (UPPM Polsub, 2020)
Abstract. Subang Regency is one of the biggest corn producing regions in West Java besides Garut and Karawang. The average corn production in Subang Regency reached 1,318.4 tons or 1.2% (2008-2012) (Darmawan, Safei, & Hamdani, 2014). The quality and quantity of corn production is influenced by the process of handling the harvest and post-harvest. Post-harvest problems that are often experienced by farmers are the shrinking of the quantity and quality of maize yields due to the corn shelling process which is still done manually so that it is less efficient and low productivity. The purpose of this research is to produce a corn sheller machine that is simple, does not take up a large place in its placement, and is relatively inexpensive and easy to maintain. The method in this research is the study of literature, reading work drawings, making work preparations, preparing tools and materials, manufacturing processes, and testing the performance of tools. The results of this study are the corn sheller machine created with dimensions of length 500 cm, width 49 cm and height 100 cm, capacity of 2 kg / minute with 1400 rpm rotation. Based on the performance test results obtained that an increase in production capacity with a corn sheller machine that is 1 minute can produce 2.7 kg of shelled corn, while manually can only produce 1 ounce or 0.1 kg in 1 minute. So the comparison is obtained manually and machine that is 1: 27. In addition, the results of shelled corn has good quality or the seeds are not damaged.Â Keywords: Corn, Shelling Machine, Manufacture